Undersedation is a risk factor for the development of subglottic stenosis in intubated children - Cláudia Schweiger; Denise Manica; Denise Rotta Rutkay Pereira; Paulo Roberto Antonacci Carvalho; Jefferson Pedro Piva; Gabriel Kuhl; Leo Sekine; Paulo José Cauduro Marostica (Brazilian Society of Pediatrics, 2017)
Objective: To analyze the level of sedation in intubated children as a risk factor for the development of subglottic stenosis (SGS). Methods: All patients between 30 days and 5 years of age who required endotracheal intubation in the pediatric intensive care unit between 2013 and 2014 were included in this prospective study. They were monitored daily and COMFORT‐B scores were obtained. Flexible fiber‐optic laryngoscopy was performed within eight hours of extubation, and repeated seven to ten days later if the first examination showed moderate to severe laryngeal injuries. If these lesions persisted and/or if the child developed symptoms in the follow‐up period, microlaryngoscopy under general anesthesia was performed to evaluate for SGS. Results: The study included 36 children. Incidence of SGS was 11.1%. Children with SGS had a higher percentage of COMFORT‐B scores between 23 and 30 (undersedated) than those who did not develop SGS (15.8% vs. 3.65%, p = 0.004). Conclusion: Children who developed SGS were less sedated than children who did not develop SGS.